Prophylactic effects of taurine and diltiazem, alone or combined, on reperfusion arrhythmias in rats - Li Ping; Kang Yi; Wang Guo-Xiang (Acta Pharmacologica Sinica, 2016)
AIM: To study the effects of taurine (Tau) and diltiazem (Dil), alone or in combination, on reperfusion arrhythmias in anesthetized rats. METHODS: The arrhythmias were produced by coronary artery ligation for 15 min followed by reperfusion. Malondialdehyde (MDA) content and superoxide dismutase (SOD) activity were measured by thiobarbituric acid fluorescence assay and colorimetric determination. RESULTS: Tau 70 mg.kg-1 in combination with Dil 1 mg.kg-1 were more effective on prevention of the reperfusion arrhythmias than each drug alone. The combination of both drugs not only decreased the content of MDA, but also increased the activity of SOD in reperfusion myocardium. CONCLUSION: The inhibition of lipoperoxides formation as well as the inhibition of the calcium influx was involved in the anti-arrhythmic effect of both Tau and Dil.